Site Plan for the Development of Hukurila Beach Tourism Object, Ambon City - Riry, Roberth Berthy; Tetelepta, Edward Gland (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Maluku is one of Indonesia's archipelagic provinces, consisting of small islands with a vast potential for marine tourism, including beautiful beach destinations. The purpose of this study is to create a site plan for the development of a beach tourism area and to analyze the impact of this development on land use. The general method used is a survey method, which includes comparative studies, interviews, and the establishment of landscape design criteria. The design method employed is based on the approach proposed by Michael Laurie, which involves three stages: site identification, site analysis, and detailed landscape design. The landscape design for the Hukurila Beach Tourism Object is viewed as part of preserving the community's social and cultural values. It embodies local customs and wisdom while maximizing surrounding resources as building materials that reflect the unique characteristics of local architecture and the natural landscape. The steep and sloping location is suitable for the development of various types of orchid cultivation, adapted to their growing conditions on soil, rocks, or trees, including Epiphytic Orchids, Terrestrial Orchids, Saprophytic Orchids, Amoebophytic Orchids, and Lithophytic Orchids.